THE ROLE OF INFORMATION TECHNOLOGY TOOLS IN INCREASING THE PROFESSIONAL TRAINING OF FUTURE ENGINEERS IN THE EDUCATIONAL PROCESS - Madaminov Abdullox Rustamjon ogli (Journals Park Publishing, 2022)
This article highlights issues related to the emergence of new technologies and software in higher educational institutions, the expansion of computer capabilities, the transition to the category of anachronism of its understanding as a computing tool, which led to the replacement of the term "computer technology" by the concept of "information technology".
Keywords: informatization; information technology; computer engineering